The American Society of Breast Surgeons and Quality Payment Programs: Ranking, Defining, and Benchmarking More Than 1 Million Patient Quality Measure Encounters - Landercasper, Jeffrey (Ann Surg Oncol, 2017)
BACKGROUND: To identify and remediate gaps in the quality of surgical care, the American Society of Breast Surgeons (ASBrS) developed surgeon-specific quality measures (QMs), built a patient registry, and nominated itself to become a Center for Medicare and Medicaid Services (CMS) Qualified Clinical Data Registry (QCDR), thereby linking surgical performance to potential reimbursement and public reporting. This report provides a summary of the program development. METHODS: Using a modified Delphi process, more than 100 measures of care quality were ranked. In compliance with CMS rules, selected QMs were specified with inclusion, exclusion, and exception criteria, then incorporated into an electronic patient registry. After surgeons entered QM data into the registry, the ASBrS provided real-time peer performance comparisons. RESULTS: After ranking, 9 of 144 measures of quality were chosen, submitted, and subsequently accepted by CMS as a QCDR in 2014. The measures selected were diagnosis of cancer by needle biopsy, surgical-site infection, mastectomy reoperation rate, and appropriateness of specimen imaging, intraoperative specimen orientation, sentinel node use, hereditary assessment, antibiotic choice, and antibiotic duration. More than 1 million patient-measure encounters were captured from 2010 to 2015. Benchmarking functionality with peer performance comparison was successful. In 2016, the ASBrS provided public transparency on its website for the 2015 performance reported by our surgeon participants. CONCLUSIONS: In an effort to improve quality of care and to participate in CMS quality payment programs, the ASBrS defined QMs, tracked compliance, provided benchmarking, and reported breast-specific QMs to the public.